2020
DOI: 10.1176/appi.ajp.2020.20070998
|View full text |Cite
|
Sign up to set email alerts
|

Disruptive Behavior Disorders: The Challenge of Delineating Mechanisms in the Face of Heterogeneity

Abstract: Causal pathways to Disruptive Behavior Disorders, even within the same diagnostic category, are varied. Both equifinality and multifinality pose considerable challenges to uncovering underlying mechanisms and understanding varied developmental trajectories associated with Disruptive Behavior Disorders. Uncovering genetic causes requires improved granularity in how we operationalise presentation and developmental trajectories associated with Disruptive Behavior Disorders. If we want to integrate the study of ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…The present findings emphasize that the assessment of early DB should include a range of behaviors to identify distinct and more finely detailed developmental trajectories (Viding & McRory, 2020). Second, they underline the importance of assessing a diversity of risk factors in order to discriminate between those common to multiple patterns of DB and those specific to one pattern or another.…”
Section: Discussionmentioning
confidence: 65%
“…The present findings emphasize that the assessment of early DB should include a range of behaviors to identify distinct and more finely detailed developmental trajectories (Viding & McRory, 2020). Second, they underline the importance of assessing a diversity of risk factors in order to discriminate between those common to multiple patterns of DB and those specific to one pattern or another.…”
Section: Discussionmentioning
confidence: 65%
“…Other studies have demonstrated that prior maltreatment experience is also associated with both social isolation and loneliness over time (Hanlon et al, 2020). This pattern of attenuated social networks following maltreatment (including both extent and quality of social relationships), relative to peers, has been termed 'social thinning' (McCrory, 2020;Viding & McCrory, 2020) and is postulated to be one factor contributing to long term psychiatric risk (Wielaard, Hoyer, Rhebergen, Stek, & Comijs, 2018). There is a need for prospective studies, incorporating experimental measures of trust, to investigate whether trust Trust and childhood maltreatment processing is one mechanism which may contribute to social thinning over time.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated that prior maltreatment experience is also associated with both social isolation and loneliness over time (Hanlon et al, 2020). This pattern of attenuated social networks following maltreatment (including both extent and quality of social relationships), relative to peers, has been termed 'social thinning' (McCrory, 2020;Viding & McCrory, 2020) and is postulated to be one factor contributing to long term psychiatric risk (Wielaard, Hoyer, Rhebergen, Stek, & Comijs, 2018). There is a need for prospective studies, incorporating experimental measures of trust, to investigate whether trust processing is one mechanism which may contribute to social thinning over time.…”
Section: Discussionmentioning
confidence: 99%